2013
DOI: 10.1104/pp.112.200147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Role of Gene Features in Determining Evolutionary Fates of Whole-Genome Duplication Duplicated Genes in Flowering Plants    

Abstract: The evolution of genes and genomes after polyploidization has been the subject of extensive studies in evolutionary biology and plant sciences. While a significant number of duplicated genes are rapidly removed during a process called fractionation, which operates after the whole-genome duplication (WGD), another considerable number of genes are retained preferentially, leading to the phenomenon of biased gene retention. However, the evolutionary mechanisms underlying gene retention after WGD remain largely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 98 publications
3
77
0
Order By: Relevance
“…Intriguingly, Amborella genes that undergo AS produce the highest average number of isoforms/gene compared to other species (Table S3). Whether this feature reflects the evolutionary position of Amborella in angiosperm, or is the result of the absence of lineage specific whole genome duplication events-whereas species with additional lineage specific WGD events have lost or partitioned AS isoforms among paralogues through subfunctionalization (Jiang et al 2013)-remains to be investigated. Maize has the largest collection of RNA-Seq data among the nine species examined, and also has the largest number of AS events, but the percentage of multi-exon genes that undergo AS is similar to other species.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, Amborella genes that undergo AS produce the highest average number of isoforms/gene compared to other species (Table S3). Whether this feature reflects the evolutionary position of Amborella in angiosperm, or is the result of the absence of lineage specific whole genome duplication events-whereas species with additional lineage specific WGD events have lost or partitioned AS isoforms among paralogues through subfunctionalization (Jiang et al 2013)-remains to be investigated. Maize has the largest collection of RNA-Seq data among the nine species examined, and also has the largest number of AS events, but the percentage of multi-exon genes that undergo AS is similar to other species.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research examined the relationships between gene features and retention probability following WGD in six plant genomes, including soybean (Jiang et al, 2013). They concluded that retained WGD genes have either low evolutionary rates (K a ) and high and broad expression patterns (type I), high structural complexity, including longer gene length, greater number of introns, and gene isoforms (type II), or high GC/GC3 content (type III).…”
Section: Methylation May Have Contributed To Biased Retention Of Genementioning
confidence: 99%
“…Since retained duplicated genes are more prone to AS (type II; Jiang et al, 2013), CG body methylation could play a role in retention if there is an explicit link with AS. Further analysis of paralogous or orthologous gene pairs that have simultaneously lost both AS and CG body methylation could help to elucidate the role of gene-body methylation in transcript splicing and its role in the evolution of duplicated genes.…”
Section: Methylation May Have Contributed To Biased Retention Of Genementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, many large enzyme families, such as aminotransferases (39), contain members that differ in function. Furthermore, plants have many paralogs resulting from wholegenome duplication events (10,40,41). To deal with these challenges, we use the Ensembl Compara protein families, which depend on phylogenetic trees to extract orthologous relationships (32,42).…”
Section: Organizing Biochemical Pathways and Protein Families Into Sumentioning
confidence: 99%